Exogenous Lipoid Pneumonia in Children: A Systematic Review and Case Series from South Africa - Marangu, Diana Mwendwa (Department of Paediatrics and Child Health, 2019)
Background and objective: To describe the clinical-radiological-pathological characteristics and treatment outcomes of childhood exogenous lipoid pneumonia (ELP) and elucidate oil administration practices. Methods: A retrospective study of children with histologically-confirmed ELP at Red Cross Children’s Hospital, South Africa. Caregivers were interviewed to understand oil administration practices. Results: Twelve children of Zimbabwean heritage aged 2.1-10.8 months were identified between 2012 and 2017. Repeated oral administration of plant-based oil for cultural reasons was reported by 10/11 caregivers. Cough (12/12), tachypnea (11/12), hypoxia (9/12) and diffuse alveolar infiltrates on chest radiography (12/12) were common at presentation. Chest computed tomography revealed ground glass opacification with lower zone predominance (9/9) and interlobular septal thickening (8/9). All bronchoalveolar lavage specimens appeared cloudy/milky, with abundant lipid laden macrophages and extracellular lipid on Oil-Red-O staining and documented polymicrobial (6/12) and Mycobacterium abscessus (2/12) co-infection. Antibiotics, systemic corticosteroids and therapeutic partial lung lavage were interventions in all, 8 and 5 patients respectively. Median time to clinical resolution was 1.1 months IQR (0.5-8.0) with radiological resolution only in 2/12 cases. Conclusions: Paediatric ELP resembles pulmonary alveolar proteinosis. Health workers should explicitly probe for a history of oil administration in children with non-resolving pneumonia and consider the diagnosis of ELP in settings where this is a common practice.